Cryptology : Classical and Modern - Klima, Richard; Klima, Richard E.; Sigmon, Neil; Sigmon, Neil P.; Taylor and Francis (Boca Raton, FL : Chapman and Hall/CRC, 2018)
Cryptology: Classical and Modern, Second Edition proficiently introduces readers to the fascinating field of cryptology. The book covers classical methods including substitution, transposition, Playfair, ADFGVX, Alberti, Vigene re, and Hill ciphers. It also includes coverage of the Enigma machine, Turing bombe, and Navajo code. Additionally, the book presents modern methods like RSA, ElGamal, and stream ciphers, as well as the Diffie-Hellman key exchange and Advanced Encryption Standard. When possible, the book details methods for breaking both classical and modern methods. The new edition expands upon the material from the first edition which was oriented for students in non-technical fields. At the same time, the second edition supplements this material with new content that serves students in more technical fields as well. Thus, the second edition can be fully utilized by both technical and non-technical students at all levels of study. The authors include a wealth of material for a one-semester cryptology course, and research exercises that can be used for supplemental projects. Hints and answers to selected exercises are found at the end of the book.
1. Introduction to Cryptology -- Basic Terminology -- Cryptology in Practive -- Why Study Cryptology? -- 2. Substitution Ciphers -- Keyword Substitution Ciphers -- Cryptanalysis of Substitution Cipher -- Playrair Ciphers -- The Navajo Code -- 3. Transposition Ciphers -- Columnar Transposition Ciphers -- Cryptanalysis of Transposition Ciphers -- ADFGX and ADFGVX Ciphers -- 4. The Enigma Machine -- The Enigma Cipher Machine -- Combinatorics -- Security of the Enigma Machine -- 5. The Turing Bombe -- Cribs and Menus -- Loops and Logical Inconsistencies -- Searching for the Correct Configuration -- The Diagonal Board -- The Checking Machine -- Turnovers -- Clonking -- Final Observations -- 6. Shift and Affine Ciphers -- Modular Arithmetic -- Shift Ciphers -- Cryptanalysis of Shift Ciphers -- Affine Ciphers -- Cryptanalysis of Affine Ciphers -- 7. Alberti and Vigenere Ciphers -- Alberti Ciphers -- Vigenere Ciphers -- Probability -- The Friedman Test -- The Kasiski Test -- Cryptanalyis of Vigenere Keyword Ciphers -- 8. Hill Ciphers -- Matrices -- Hill Ciphers -- Cryptanalyis of Hill Ciphers -- 9. RSA Ciphers -- Introduction to Public-Key Ciphers -- Introduction to RSA Ciphers -- The Euclidean Algorithm -- Modular Exponentiation -- ASCII -- RSA Ciphers -- Cryptanalyis of RSA Ciphers -- Primality Testing -- Integer Factorization -- The RSA Factoring Challenges -- 10. ElGamal Ciphers -- The Diffie-Hellman Key Exchange -- Discrete Logarithms -- ElGamal Ciphers -- Cryptanalyis of ElGamal Ciphers -- 11. The Advanced Encryption Standard -- Representations of Numbers -- Sream Ciphers -- AES Preliminaries -- AES Encryption -- AES Decryption -- AES Security -- 12. Message Authentication -- RSA Signatures -- Hash Functions -- RSA Signatures with Hashing -- The Man-in-the-Middle Attack -- Public-Key Infrastructures -- Bibliography -- Hints and Answers for Selected Exercises -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: MATHEMATICS / Recreations & Games; MATHEMATICS / Combinatorics; classical ciphers; cryptanalysis; cryptographic algorithms; cryptology textbook; Enigma cipher machine; Introduction to Cryptology; Maplet-based examples; Message Authentication; mathematics in cryptology; Navajo code; public-key cryptography; U.S. cryptographic standards; Cryptography; Cryptography -- Data processing; Data encryption (Computer science); Ciphers; Electronic books